2019
DOI: 10.1136/ijgc-2019-000387
|View full text |Cite
|
Sign up to set email alerts
|

Triple tracer (blue dye, indocyanine green, and Tc99) compared to double tracer (indocyanine green and Tc99) for sentinel lymph node detection in endometrial cancer: a prospective study with random assignment

Abstract: ObjectiveSentinel lymph node (SLN) mapping is increasingly being used in the treatment of apparent early-stage endometrial cancer. The aim of this study was to evaluate whether three tracers (blue dye, indocyanine green (ICG), and technetium-99 (Tc99)) performed better than two (ICG and Tc99).Study DesignProspective study of all consecutive patients (n=163) diagnosed with clinical early-stage endometrial cancer from 2015 to 2017. All patients were randomly assigned to receive a mixture of ICG and Tc99 with or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
11
0
2
Order By: Relevance
“…Recently, Kessous et al reported a series of 157 patients who were randomly assigned to receive ICG and Tc-99m or ICG, Tc-99m, and blue dye. They reported an overall detection rate of 97% and a bilateral detection rate of 81% within the cohort of ICG and Tc-99m, and concluded that the use of a triple combination of tracers does not improve any of the parameters obtained with ICG and Tc-99m 26…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Kessous et al reported a series of 157 patients who were randomly assigned to receive ICG and Tc-99m or ICG, Tc-99m, and blue dye. They reported an overall detection rate of 97% and a bilateral detection rate of 81% within the cohort of ICG and Tc-99m, and concluded that the use of a triple combination of tracers does not improve any of the parameters obtained with ICG and Tc-99m 26…”
Section: Discussionmentioning
confidence: 98%
“…How et al (14) used mixture of all three tracers and found that ICG and Tc99m-FSC had similar rates of overall and bilateral SLN detection. Kessous et al (15) reported higher unilateral and bilateral SLN detection rates of 97.5% and 81.3%, respectively, with concomitant use of ICG and Tc99m-FSC. Recently, Cabrera et al (16) demonstrated significantly higher bilateral detection rate among patients injected with Tc-99m and ICG patients (69%).…”
Section: Discussionmentioning
confidence: 99%
“…A combination of ICG with Tc99m nanocolloid to show and detect sentinel lymph nodes in patients with endometrial cancer has recently come into the focus of scientific interest. Kessous et al reported in their study of 157 patients with endometrial cancer that a triple tracer combination (ICG, Tc99m and patent blue) does not lead to a significant improvement in the overall detection rate (93.5 vs. 97.5%) and bilateral detection rate (80.5 vs. 81.3%) compared with a double tracer combination (ICG and Tc99m) 42 . In a group of 84 patients with endometrial cancer Cabrera et al compared the sentinel lymph node detection rate after mapping by a combination of ICG and Tc99m (35 patients) to mapping with the combination of ICG and methylene blue (49 patients) 43 .…”
Section: Technical Aspects Of Sentinel Lymph Node Biopsy: Which Tracer/which Dye?mentioning
confidence: 97%
“…Eine Kombination von ICG mit Tc99m-Nanokolloid zur Darstellung und Detektion der Sentinellymphknoten bei Patientinnen mit Endometriumkarzinom ist erst vor Kurzem in den Fokus des wissenschaftlichen Interesses gerückt. Kessous et al berichteten in ihrer Studie mit 157 Patientinnen mit Endometriumkarzinom, dass eine 3-fache Tracer-Kombination (ICG, Tc99m und Patentblau) verglichen mit einer 2-fachen Tracer-Kombination (ICG und Tc99m) nicht zu einer signifikanten Verbesserung der Gesamtdetektionsrate (93,5 vs. 97,5%) und bilateralen Detektionsrate (80,5 vs. 81,3%) führt 42 . Cabrera et al haben in einem Kollektiv von 84 Patientinnen mit Endometriumkarzinom die Detektionsrate der Sentinellymphknoten nach Darstellung mittels einer Kombination von ICG und Tc99m (35 Patientinnen) mit der Kombination von ICG und Methylenblau (49 Patientinnen) verglichen 43 .…”
Section: Technische Aspekte Der Sentinellymphonodektomie: Welcher Tracer/welcher Farbstoff?unclassified